Jensen’s operator inequality and its converses - Hansen, Frank; Pecaric, Josip; Peric, Ivan (MATHEMATICA SCANDINAVICA, 2007)
We give a general formulation of Jensen’s operator inequality for unital fields of positive linear mappings, and we consider different types of converse inequalities.